PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MEMBUAT MEDIA PEMBELAJARAN SD NEGERI 010 PULAU TERAP KABUPATEN KAMPAR - Syamsurizal Syamsurizal (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is a study of school action against the lack of ability of teachers in making learning media, for itapplied the method of giving tasks with the aim to improve the ability of teachers in making learning media. Thisresearch was conducted in SD Negeri 10 Pulau Terap, this research was conducted two cycles with stages:planning, implementation, observation, and reflection. The result of research stated that the ability of teachersin making learning media has increased. This is seen in the first cycle of 65% with good category and in thesecond cycle increased to 89% with very good category. Based on these data it can be concluded that theapplication of the method of assignment can improve the ability of teachers in making learning media.